Penerapan Konsumsi Islami Dalam Pandangan Maqashid Syariah - Arifudin Arifudin; Muhamad Sidqi Mauludin; Rofi Uddarojat; Prasetiyo Yulianto; Muhammad Rifqi Hidayat (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
Islamic consumption is the activity of using or utilizing goods or services that are guided by Islamic values. There has been a lot of research that examines Islamic consumption, but there is still little research that discusses Islamic consumption from the perspective of Markash law. Documentary research is a research method where the researcher is present and plays a role in collecting data, processing data, presenting and analyzing data, and writing conclusions. The findings show that Islamic consumption must adhere to principles such as sharia or divine principles, the principle of quantity accuracy, the principle of prioritization of needs, and moral principles. Meanwhile, in Islamic law, Islamic consumption must be able to achieve the preservation of religion, the preservation of lineage, the preservation of reason, the preservation of soul, and the preservation of property. All the principles contained in Islamic consumption are intended to make Muslim consumption a form of worship, provide benefits and eliminate evil in accordance with sharia law.